Chromosome-scale assembly of wild barley accession "OUH602". Issue 10 (13th July 2021) - Sato, Kazuhiro; Mascher, Martin; Himmelbach, Axel; Haberer, Georg; Spannagl, Manuel; Stein, Nils
Abstract: Barley ( Hordeum vulgare ) was domesticated from its wild ancestral form ca. 10, 000 years ago in the Fertile Crescent and is widely cultivated throughout the world, except for in tropical areas. The genome size of both cultivated barley and its conspecific wild ancestor is approximately 5 Gb. High-quality chromosome-level assemblies of 19 cultivated and one wild barley genotype were recently established by pan-genome analysis. Here, we release another equivalent short-read assembly of the wild barley accession "OUH602." A series of genetic and genomic resources were developed for this genotype in prior studies. Our assembly contains more than 4.4 Gb of sequence, with a scaffold N50 value of over 10 Mb. The haplotype shows high collinearity with the most recently updated barley reference genome, "Morex" V3, with some inversions. Gene projections based on "Morex" gene models revealed 46, 807 protein-coding sequences and 43, 375 protein-coding genes. Alignments to publicly available sequences of bacterial artificial chromosome (BAC) clones of "OUH602" confirm the high accuracy of the assembly. Since more loci of interest have been identified in "OUH602, " the release of this assembly, with detailed genomic information, should accelerate gene identification and the utilization of this key wild barley accession.